CENDANA Nusa Tenggara Timur / S. Agung Sri Raharjo...[et.al]; editor, Lukas Rumboko W., S. Agung Sri Raharjo - AGUNG SRI RAHARJO, S.; LUKAS RUMBOKO W. (Gadjah Mada University Press, 2017)
xxii, 126 hlm. : ilus. ; 23 cm.